2020
DOI: 10.3389/fnbeh.2020.558074
|View full text |Cite
|
Sign up to set email alerts
|

The Projection From Ventral CA1, Not Prefrontal Cortex, to Nucleus Accumbens Core Mediates Recent Memory Retrieval of Cocaine-Conditioned Place Preference

Abstract: Drug-paired cues inducing memory retrieval by expressing drug-seeking behaviors present a major challenge to drug abstinence. How neural circuits coordinate for drug memory retrieval remains unclear. Here, we report that exposure of the training chamber where cocaine-conditioned place preference (CPP) was performed increased neuronal activity in the core of nucleus accumbens (AcbC), ventral CA1 (vCA1), and medial prefrontal cortex (mPFC), as shown by elevated pERK and c-Fos levels. Chemogenetic inhibition of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…DH and VH differ greatly in development, anatomy, circuitry, molecular characteristics, synaptic plasticity, and function [10,22] . Although both are involved in the memory process of MOR addiction, several studies in recent years have suggested that VH plays an important role in the mechanisms of nicotine [22] , cocaine [23] and opioid addiction [6,7,11,24] . The present study further proved that the change of VH-β and γ band power is directly related to the extinction of opioid addiction and the extinction method.…”
Section: Discussionmentioning
confidence: 99%
“…DH and VH differ greatly in development, anatomy, circuitry, molecular characteristics, synaptic plasticity, and function [10,22] . Although both are involved in the memory process of MOR addiction, several studies in recent years have suggested that VH plays an important role in the mechanisms of nicotine [22] , cocaine [23] and opioid addiction [6,7,11,24] . The present study further proved that the change of VH-β and γ band power is directly related to the extinction of opioid addiction and the extinction method.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GRIP1 is involved in both cocaine-associated learning and memory, consistent with the finding that GRIP1 regulates electric shock-related learning and memory in the hippocampus ( Tan et al, 2020 ). Meanwhile, the circuit from the hippocampal CA1 to the NAc mediates cocaine-associated memory ( Zhou et al, 2019 , 2020 ); hence, GRIP1 in the NAc may be involved in this circuit to adjust learning and memory in cocaine-induced CPP behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidences indicating the role of the NAc shell in the acquisition of CPP [ 31 , 51 ]. However, there are also studies showing the involvement of the NAc Core too [ 31 , 52 54 ]. In addition, some studies have shown the role of whole NAc in this issue including our previous studies [ 5 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%